PUBLIC IMPRESSIONS OF THE USE OF SHARIA PEER-TO-PEER LENDING IN PREVENTING ILLEGAL ONLINE LOAN FRAUD - Nurul Aisah; Nur Rahmawati; Sisca Dian Rahmawati; Dewangga Eka Syahputra; Aulia Galuh Ani Sekar Arum (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya(STIESIA) Surabaya, 2024)
Interest in sharia loans may be significantly lower than regular internet loans. Online Sharia loans are safer than conventional loans as they do not incur interest or usury and do not impose penalties for late payments. This study seeks to ascertain public perceptions regarding the utilization of Sharia-compliant P2P lending as a means to mitigate illicit online loan fraud. The employed methodology is a mixed methods research strategy, specifically quantitative utilizing the TAM model and qualitative through structured interviews, aimed at acquiring deeper insights from relevant sources. This research sample used 167 respondents with the criteria namely people who have knowledge or experience using Sharia P2P Lending. The research findings indicate that trust and comfort affect individuals' views and interest in utilizing P2P syariah lending. Attitudes affect individuals' desire to utilize Sharia P2P Lending, whereas risk perceptions do not influence their attitudes or interests. Moreover, the significance of Sharia P2P Lending is paramount, as it functions by Sharia principles that prioritize justice, transparency, and the avoidance of usury, gharar, and maysir. Digital literacy, particularly in financial matters, is essential to avert illicit online loan fraud.